Green hydrothermal approach for the synthesis of carbon quantum dots from waste tea bags for acrylamide detection in drinking water: A fluorescence assay validated by HPLC-PDA analysis - Nikhil Sharma; Sweezee Thakur; Aarti Bains; Gulden Goksen; Nemat Ali; Mushtaq Ahmad Ansari; Anna Kopsacheili; Charalampos Proestos; Prince Chawla (Food Chemistry: X)
The study focused on converting tea bag waste into strong fluorescence carbon quantum dots (TBW-CQDs) for the detection of acrylamide in drinking water, antimicrobial activity, and photocatalytic degradation. The TBW-CQDs exhibited blue luminescence and maximum absorbance at 287 nm under UV light and distinctive fluorescence emission and excitation wavelengths at 425 nm and 287 nm, respectively. TBW-CQDs revealed a particle size of 8.12 ± 0.06 nm with a spherical morphology followed by an abundance of 59.29 % carbon and 39.82 % oxygen. For acrylamide extraction from water, the QuEChERS method was established, which exhibited a recovery rate of 97 to 99 %. The fluorescence-based sensor exhibited a low limit of detection of 0.35376 ppm, which was validated by HPLC-PDA (LOD 0.300688 ppm). TBW-CQDs degraded 90.62 % of indigo carmine and 93.19 % of methylene blue under bright sunlight. In conclusion, the fabricated TBW-CQDs provide a promising, cost-effective, and precise approach to acrylamide detection in drinking water.